Predicting psychological need satisfaction from differential coach treatment: Does receiving more of the coach`s attention than teammates matter? - Stuntz, C. P.; Boreyko, C. L. (International Journal of Sport and Exercise Psychology, 2018)
This study examined whether differential treatment that individual athletes perceive predicted psychological need satisfaction. Perceiving more frequent interactions of all types (including both more positive instructive and supportive behaviours as well as more negative rapport) than other individuals on the team received were hypothesised to relate to higher basic psychological need fulfilment. Collegiate athletes (N= 249) completed surveys assessing coach treatment to them and to other individuals on the team regarding technical skills instruction, how well coaches knew about athletes` lives outside of sport, and negative rapport as well as assessing perceived competence, autonomy, and relatedness. Similar to hypotheses yet counter-intuitive to many, those athletes who believed they received more negative rapport than others on the team received also perceived greater relatedness and autonomy, while those athletes who believed their coach knew and cared about all aspects of their lives outside of sport more than the coach did for others on the team perceived greater competence and relatedness. How athletes are treated in comparison to how teammates are treated matters, even after accounting for coach treatment towards athletes themselves in analyses.